HYDATID CYST OF THE UTERINE CERVIX - Dhaifalah, Ishraq (Biomedical papers, 2001)
I report and discuss a very rare case of primary involvement of the uterine cervix by hydatid cyst a parasiticdisease caused by Echinococcus granulosus, whose first and most important site is the liver. The case wasmisdiagnosed as an ovarian cyst until the time of operation.And this is to alert the gynaecologist to the possibility of hydatid cyst when a septated mass is found in the pelvis.
Keywords: Hydatid cyst / Uterine cervix / Localisation / Diagnosis / Treatment